Drag reduction on a flat-back ground vehicle with active flow control. Issue 145 (October 2015) - McNally, Jonathan; Fernandez, Erik; Robertson, Gregory; Kumar, Rajan; Taira, Kunihiko; Alvi, Farrukh; Yamaguchi, Yoshihiro; Murayama, Kei
Abstract: Active flow control is applied to the Honda Simplified Body (HSB), a flat-back ground vehicle model, for aerodynamic drag reduction. The use of small scale, steady jets (microjets) in normal and tangential injection orientations is investigated through experimental parametric studies and companion numerical simulations. Parameters such as injection location relative to separation point, jet diameter, and blowing ratio are explored. The flow response is characterized experimentally by aerodynamic force measurements and velocity field measurements. The computational effort utilizes Large Eddy Simulation (LES) to uncover how flow control with a steady microjet array modifies the wake and the corresponding drag. The impact of the microjets on the baseline flow field is discussed. The computational study introduces the actuator array on the top surface of the model body to support the experimental study that examines the effectiveness of flow control with microjets installed on multiple side surfaces. From both experimental and numerical analyses, it is observed that the wake can be modified with microjets such that the drag experienced by the HSB is reduced by nearly 3% with net reduction in power consumption. Abstract : Highlights: Use of low mass flux, high momentum microjets as a vehicular wake control device. Parametric studies of control over a range of array configurations and conditions. Examination of modifications to the flow field and corresponding aerodynamic forces. Analysis of efficiency and change in power consumption due to microjet control. Integrated experimental and computational (LES) studies.